IDENTIFIKASI SENYAWA BAHAN ALAM SEBAGAI INHBITOR TIROSIN KINASE EGFR: SKRINING IN SILICO BERBASIS FARMAKOFOR DAN MOLECULAR DOCKING - Frangky Sangande; Jonly Piere Uneputty (Faculty of Pharmacy, Universitas Muslim Indonesia, 2021)
Epidermal growth factor receptor (EGFR) is one of tyrosine kinase that overexpressed in many types of cancer. The ihbiition of EGFR activity has known as a rational target for cancer therapy. However, several EGFR inhibitors have limitations related to resistance problems or reduced tumor response. Therefore, the effort to develop new inhibitors with greater efficacy is very important to overcome the problems. In the present study, we designed a computational method by combining ligand based pharmacophore modeling and molecular docking for screening the potential natural compounds as EGFR inhibitors. Validation result of ligand based pharmacophore modeling and docking molecular by ROC curves showed that both of these protocols had AUC ≥ 0.7. The Redocking erlotinib to EGFR in our docking protocols gave the RMSD < 2 Å. Therefore, our computational method could be applied for virtual screening. Initial screening based on pharmacophore modeling obtained 86 out of 179.816 compounds that could be mapped with the pharmacophore features. Further screening through molecular docking showed two compounds had a lower docking score than erlotinib, i.e ZINC00941342 and ZINC72325782. However, by careful analysis of their interaction profiles, only ZINC00941342 which formed hydrogen bonds with Met769, which is known as an EGFR key residue. Additionally, it was also found to form hydrogen with Cys773. Therefore, we recommend ZINC00941342 as a potential EGFR inhibitor.